GOAT MILK PRODUCTION UNDER ORGANIC FARMING STANDARS - Gerold Hartmut Rahmann (Tropical and Subtropical Agroecosystems, 2009)
Organic farming has emerged from its niche. This holds true for organic goat milk, yoghurt and cheese as well. Particularly in the EU many dairy goat farms have converted or want to convert towards organic farming to profit from the positive image and the good prices for milk (+100% in Western Europe and Alpine regions). High performance dairy goats demand excellent feedstuffs, a sound environment and top management. It was not clear how organic farming can fulfil these demands. The restrictive factors influencing the productivity of the animals in organic farming are as follows: limited concentrate feeding (